Reptiles and Amphibians - Ramiro Aguillón Gutiérrez, David (IntechOpen, 2018)
The book Reptiles and Amphibians is a compilation of the current trends in herpetology, focusing on evolution, physiology, monitoring, bioacoustics, threats, and conservation biology. All the chapters present an interesting aspect of the biology of reptiles and amphibians, encompassing different groups of these animals such as frogs, toads, newts, chelonians and snakes from various parts of the world. Without a doubt, this book will help to keep updated on the current problems that arise in this interesting biological group.